2009
DOI: 10.1148/radiol.2512080384
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for Coronary CT Angiography: What Constitutes Sufficient Training?

Abstract: Increasing experience with coronary CT angiography improved the diagnostic performance of inexperienced physicians. However, acquiring expertise in coronary CT angiography was slow and may take more than 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 27 publications
5
44
0
Order By: Relevance
“…[2][3][4][5][6] Beyond stenosis, CTA also permits noninvasive assessment of atherosclerotic plaque and coronary artery remodeling. [7][8][9] Current clinical assessment of CTA and lesion detection is based on visual analysis, which is time consuming and subject to observer variability, 10 although computer-aided extraction of the coronary arteries is often employed. 11 It was reported that acquiring expertise in CTA interpretation may take more than a year.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Beyond stenosis, CTA also permits noninvasive assessment of atherosclerotic plaque and coronary artery remodeling. [7][8][9] Current clinical assessment of CTA and lesion detection is based on visual analysis, which is time consuming and subject to observer variability, 10 although computer-aided extraction of the coronary arteries is often employed. 11 It was reported that acquiring expertise in CTA interpretation may take more than a year.…”
Section: Introductionmentioning
confidence: 99%
“…Their ability to evaluate significant coronary stenoses can improve after one year of training with approximately 600 cases a year. An increase of sensitivity is seen after one year of training, ranging from 66%-75% (31). Published research about diagnostic performance was almost always carried out by physicians with 3 or more years of experience, resulting in a sensitivity of 90%.…”
Section: Discussionmentioning
confidence: 99%
“…These results prove CCTA a viable alternative with very high negative predictive value. However, reading CCTA images requires substantial experience and only well-trained physicians are able to interpret CCTA reliably [12]. An automated system that can rule out clinically-relevant stenoses (grade> 50%) in the coronary arteries could be used as a second reader in the absence of an expert physician in the emergency department.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, coronary arteries follow long and treacherous paths, extending over only a few voxels in diameter in the distal parts. Even experts sometimes struggle to give a correct diagnosis due to these challenges [12].…”
Section: Introductionmentioning
confidence: 99%